Pengaruh Google Sites Terhadap Hasil Belajar Siswa di SMA Negeri 3 Maros - Nur Maulidyah; Mugnilily Oktarina S; Nasir Nasir (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
Google sites is a platform in the form of a website that can be used in the learning process. This research was conducted to determine the influence of Google Sites on student learning outcomes at SMA Negeri 3 Maros, on ICT subject matter. The subjects of this research were 35 students. This research uses a quantitative type of research with a pre-experimental one group pretest and posttest approach. Research data was collected using tests that were given twice, namely before the treatment (pretest) and after the treatment (posttest). So based on the results of data analysis, researchers know that there is an increase in student learning outcomes after studying ICT using Google Sites as media. It is shown that the average posttest score (93.42%) is greater than the pretest score (80.74%), there is an increase of 12.68%. Therefore, it can be concluded that the Google Sites learning media has an influence on the learning outcomes of class X6 at SMA Negeri 3 Maros.